EXPERIMENTAL METHOD FOR SPRAY VELOCITY FIELD PREDICTION MODEL IN PRESSURE SWILL ATOMIZERS - Souza, E. J. J.; Ponte, M. J. J. S. (Revista de Engenharia Térmica, 2010)
Pressure swill atomizers are widely used in engineering as an effective device for vaporization and liquid mass transfer in physical or chemical processes. Among many applications those atomizers are used in modern fuel injection systems for spark engines. An even fuel and air mixture may increase the overall engine performance by higher efficiency and low flue gas emissions. In applied atomization, one of the most important characteristics is the spray velocity field prediction. Droplet sizing models are also important, but they are relatively popular on books and papers. By the other hand spray velocity field prediction and profile is relatively rare. This work focus on the prediction of the velocity field of pressure swirl atomize by means of an experimental approach and applied statistics. For the spray measurements this study used a non-intrusive, quantitative method by Laser Doppler Interpherometry (LDI) for the spray velocity field and droplet sizing. Also four models for the film thickness calculation at atomizer discharge are compared considering their statistical significance.